Endodontic microsurgery using NeoPutty® as a retrograde filling material: a case report - Carbajal Pimentel, Claudia Fernanda (2025)
Apical periodontitis is a chronic inflammatory condition of the periradicular tissues that occurs predominantly in previously endodontically treated teeth. Endodontic microsurgery is a specialized procedure that involves resection of the apical portion of the root, retrograde cavity preparation, and sealing with a retrograde filling material to promote periapical healing. This report describes the case of a patient whose tooth #14, previously treated for asymptomatic apical periodontitis, underwent endodontic microsurgery using the bioceramic material NeoPutty® as the retrograde filling material. At 12-month follow-up, the patient remained asymptomatic, with radiographic evidence of periapical repair and bone formation over the bioceramic material. This case suggests that endodontic microsurgery in a tooth with a post and apical periodontitis may be associated with favorable outcomes, avoiding the complications associated with post removal. Nevertheless, because this is a single case, the findings should be interpreted with caution.